Theoretical analysis of propensity to risk - Chuprikova E. V. (Education and science in the modern context, 2019)
The article provides a theoretical analysis of the main aspects of propensity to risk. A distinction is made between the concepts of "personal risk", "risk willingness", "propensity to risk". The model of "ascent to risk" by V. A. Petrovsky and his view on the phenomenon of risk propensity are considered.
Keywords: риск; risk; склонность к риску; propensity for risk; личностный риск; готовность к риску; personal risk; willingness to take risks